Threat-related motivational disengagement: Integrating blunted cardiovascular reactivity to stress into the biopsychosocial model of challenge and threat. Issue 4 (3rd July 2020) - Hase, Adrian; aan het Rot, Marije; de Miranda Azevedo, Ricardo; Freeman, Paul
ABSTRACT: Background: The biopsychosocial model of challenge and threat specifies a challenge-threat continuum where favorable demand-resource evaluations, efficient cardiovascular responses, and superior performance characterize challenge; and maladaptive outcomes like clinical depression characterize threat states. The model also specifies task engagement, operationalized as heart rate and ventricular contractility increases, as a prerequisite for challenge and threat states. The blunted cardiovascular reactivity to stress literature describes reductions of these increases and associates them with problems like clinical depression. Objectives: To determine whether blunted cardiovascular reactivity to stress has implications for challenge and threat theory. Methods: We review and synthesize the literatures on blunted cardiovascular reactivity to stress and the biopsychosocial model. Results: Blunted cardiovascular reactivity appears not to reflect a physiological inability to respond to stress. Rather, it reflects a contextually dependent motivational dysregulation and reduced reactivity to stress consistent with deficient task engagement in the biopsychosocial model. Conclusion: We argue that blunted cardiovascular reactivity represents deficient task engagement, and more generally, motivational disengagement due to threat states. Our biopsychosocial model-based approach conceptualizes this motivational disengagement as a tendency to avoid motivated performance situations. This tendency may represent a defense mechanism against subsequent threat and might explain associations with disorders like clinical depression.